Impacto da COVID-19 sobre a função tireoidiana de crianças e adolescentes: uma revisão integrativa - Uliana Pereira da Silva Lisboa; João Pedro Pereira Brito; Lucimar Retto da Silva de Avó; Debora Gusmão Melo; Carla Maria Ramos Germano (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: To evaluate changes in thyroid function associated with COVID-19 in pediatric patients, their etiology, clinical and laboratory profiles, as well as evolution. METHODS: we ran a search in PubMed, Scielo, Lilacs and Google Scholar databases, between January 2020 and July 2022, through the combination of the keywords: COVID-19, thyroid function, and pediatric population, in accordance with MeSH and DeSC, and in Portuguese, English and Spanish. RESULTS: After applying the inclusion and exclusion criteria, 8 of the 842 papers found were considered eligible for review, totaling a sample of 288 patients, aged 1 month to 18 years, affected by different forms of thyroid disfunctions related to COVID-19, including subacute thyroiditis, TSH elevation in patients with pediatric multisystem inflammatory syndrome, euthyroid sick syndrome, and autoimmune hyper or hypothyroidism diagnosed after COVID-19 or exacerbated by the infection. The papers suggest that periodic assessment of thyroid function in children and adolescents affected by COVID-19 may enable screening of asymptomatic patients and early clinical conditions associated to thyroid pathology in the post-SARS-CoV-2 infection period. CONCLUSIONS: The analyzed papers, despite their small number, are relevant because they describe illustrative cases of thyroid dysfunction related to COVID-19 infection in the pediatric population. This study also points to the need for further studies in children and adolescents to define more precisely the evolution of these thyroid disfunctions, the best way to investigate them, and their most appropriate management, considering that thyroid function is essential for a full pediatric development.